A new species of Aspalathus (Fabaceae, Crotalarieae) from the Cape Floristic Region, South Africa - Stirton, Charles H.; Preez, Brian Du; Helme, Nick; Muasya, Muthama (Phytotaxa, 2024)
A new species from the Western Cape, South Africa is described: Aspalathus praetermissa—a highly localized and critically endangered endemic, occurring between Elandsbaai, Redelinghuys, and Paleisheuwel. This species is morphologically similar to A. quinquefolia subsp. virgata, but differs in having small, 5.5–6.0 mm long, pale yellow flowers (versus flowers 7–10 mm long, bright yellow); more extensive pubescence on wing petals as well as keel petals, blade not flaring apically (versus wing petals partially pubescent to glabrous, flaring apically). A composite plate and map for A. praetermissa are presented, and a taxonomic key to the A. quinquefolia complex.